1996
DOI: 10.1515/mgmc.1996.19.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lead(iv) Reagents for Carbon-Carbon Bond Formation

Abstract: The isolation and characterisation of a range of lead(IV) complexes, prepared from achiral and chiral dicarboxylic acids, is described. These compounds have been found to bestable amorphous solids, but upon reaction with phenylboronic acid and a variety of ß-dicarbonyl substrates with mercury(ll) catalysis, carbon-carbon bond formation can be readily achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…20 In other work, we have also found that the chiral complexes 1-4 (Scheme 2) do not induce efficient asymmetry transfer in phenylation reactions of b-dicarbonyl substrates (Scheme 3 ; e.e. values in the range 4È12% are observed).20,21 This is surprising given the well documented8,9 mechanism of these phenylations which involves reductive elimination from the lead(IV) intermediate 5, produced by BÈPb transmetallation, followed by ligand exchange with the dicarbonyl nucleophile, a reaction which would be expected to be acutely sensitive to its surrounding ligand environment.…”
Section: Methodsmentioning
confidence: 92%
“…20 In other work, we have also found that the chiral complexes 1-4 (Scheme 2) do not induce efficient asymmetry transfer in phenylation reactions of b-dicarbonyl substrates (Scheme 3 ; e.e. values in the range 4È12% are observed).20,21 This is surprising given the well documented8,9 mechanism of these phenylations which involves reductive elimination from the lead(IV) intermediate 5, produced by BÈPb transmetallation, followed by ligand exchange with the dicarbonyl nucleophile, a reaction which would be expected to be acutely sensitive to its surrounding ligand environment.…”
Section: Methodsmentioning
confidence: 92%
“…Redox catalysts , are used for the electrochemically controlled conversion of molecules via a redox process that, in the absence of the catalyst, would only react under much more extreme conditions to yield, if at all, the same amount and type of product. The Pb 4+/2+ redox couple is an example of a reagent with a broad spectrum of stoichiometric uses in organic chemistry , especially with recent advances in synthetically useful carbon−carbon coupling processes and for which a recycling procedure, for example by electrochemical means under mild conditions at an electrode surface, would be highly desirable.…”
Section: Introductionmentioning
confidence: 99%